Highly discriminating protein-protein interaction specificities in the context of a conserved binding energy hotspot. - Li, W; Keeble, A; Giffard, C; James, R; Moore, G; Kleanthous, K (2004)
We explore the thermodynamic basis for high affinity binding and specificity in conserved protein complexes using colicin endonuclease-immunity protein complexes as our model system. We investigated the ability of each colicin-specific immunity protein (Im2, Im7, Im8 and Im9) to bind the endonuclease (DNase) domains of colicins E2, E7 and E8 in vitro and compared these to the previously studied colicin E9. We find that high affinity binding (Kd < or = 10(-14) M) is a common feature of cognate colicin DNase-Im protein complexes as are non-cognate protein-protein associations, which are generally 10(6)-10(8)-fold weaker. Comparative alanine scanning of Im2 and Im9 residues involved in binding the E2 DNase revealed similar behaviour to that of the two proteins binding the E9 DNase; helix III forms a conserved binding energy hotspot with specificity residues from helix II only contributing favourably in a cognate interaction, a combination we have termed as "dual recognition". Significant differences are seen, however, in the number and side-chain chemistries of specificity sites that contribute to cognate binding. In Im2, Asp33 from helix II dominates colicin E2 specificity, whereas in Im9 several hydrophobic residues, including position 33 (leucine), help define its colicin specificity. A similar distribution of specificity sites was seen using phage display where, with Im2 as the template, a library of randomised sequences was generated in helix II and the library panned against either the E2 or E9 DNase. Position 33 was the dominant specificity site recovered in all E2 DNase-selected clones, whereas a number of Im9 specificity sites were recovered in E9 DNase-selected clones, including position 33. In order to probe the relationship between biological specificity and in vitro binding affinity we compared the degree of protection afforded to bacteria against colicin E9 toxicity by a set of immunity proteins whose affinities for the E9 DNase differed by up to ten orders of magnitude. This analysis indicated that the Kd required for complete biological protection is <10(-10)M and that the "affinity window" over which the selection of novel immunity protein specificities likely evolves is 10(-6)-10(-10)M. This comprehensive survey of colicin DNase-immunity protein complexes illustrates how high affinity protein-protein interactions can be very discriminating even though binding is dominated by a conserved hotspot, with single or multiple specificity sites modulating the overall binding free energy. We discuss these results in the context of other conserved protein complexes and suggest that they point to a generic specificity mechanism in divergently evolved protein-protein interactions.